Music Lyrics and Influence on Teen Sex - Donna Davis (EDIS)
“As a baby boomer, I was part of the generation that grew up with rock and roll. I recall the first time I heard my mother respond to explicit lyrics my older brother was listening to and thinking what a renegade he was. They weren’t nearly as explicit as the lyrics of today’s music, and while I swore that I’d never become my mother, I now find myself fighting with my children to turn it off! Perhaps mom was not so far off-base after all!” This 2-page Family Album Radio transcript was written by Donna Davis and published by the UF Department of Family, Youth and Community Sciences, March 2012.